2017
DOI: 10.4067/s0034-98872017001201535
|View full text |Cite
|
Sign up to set email alerts
|

Actividad física y perfil de estilos de vida promotores de la salud en adultos mayores chilenos

Abstract: Background Part of having healthy lifestyles should be a regular practice of physical activities. Aim To evaluate the association between the practice of physical activity and healthy lifestyles in older people. Material and Methods The Health-Promoting Lifestyle Profile survey was applied to 1688 older people living in the community, aged 72 ± 7 years (61% women). This survey includes questions about regular physical activity. Results Twenty four percent of surveyed participants declared to practice physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
3
0
6
Order By: Relevance
“…Regarding the association of mild personal accomplishment and lower odds of having high waist circumference, other studies reported similar findings by showing that low personal accomplishment was associated with sedentarism in adults [38]. Sedentarism may lead to increased waist circumference and overweight.…”
Section: Discussionmentioning
confidence: 70%
“…Regarding the association of mild personal accomplishment and lower odds of having high waist circumference, other studies reported similar findings by showing that low personal accomplishment was associated with sedentarism in adults [38]. Sedentarism may lead to increased waist circumference and overweight.…”
Section: Discussionmentioning
confidence: 70%
“…La actividad física regular puede ser considerada como uno de los elementos más importantes para la salud de las personas, especialmente, en adultos mayores, puesto que, favorece la reducción de factores de riesgo generales y de mortalidad. En este sentido, los resultados del estudio en adultos mayores realizado en Santiago de Chile el año 2017 11 son coincidentes con trabajos previos, entre los cuales destaca un metaanálisis para evaluar los efectos antidepresivos del ejercicio en adultos mayores, utilizando datos de ensayos controlados aleatorios del año 2016 y otro metaanálisis donde, se investiga los beneficios inducidos por el ejercicio en aspectos específicos de la función ejecutiva en diferentes subgrupos de edad sobre la base de datos de 40 estudios experimentales. En ambos, se concluye que los adultos mayores que ostentan mayor actividad física, poseen también, más probabilidades de presentar un mejor estilo de vida 25,26 .…”
Section: Discussionunclassified
“…Estos pueden ser considerados como saludables o nocivos para la salud. La clasificación depende de cómo los EV influyen en la prevención o aparición de enfermedades (Durán, Sánchez, Valladares, López, Valdés Badilla, & Herrera, 2017).…”
Section: Introductionunclassified
“…La adopción de determinadas actividades incluidas dentro de los EV dependerá de múltiples factores. Dentro de los factores que son considerados como influyentes en la adopción de determinado patrón de conducta relacionada con los EV se señalan las costumbres adquiridas, las necesidades económicas, sociales, religiosas y culturales, así como el estado de salud de la persona determinado por la presencia de enfermedades crónicas no transmisibles (ECNT) (Durán, Sánchez, Valladares, López, Valdés Badilla, & Herrera, 2017).…”
Section: Introductionunclassified